Chemical Biology of G-quadruplex and i-motif DNA: use of topologically constrained DNA - Dejeu, Jérôme; Defrancq, Eric (Comptes Rendus. Chimie)
Tetrameric DNA structures such as G-quadruplex (G4) and i-motif (i-DNA) have attracted increasing interest in the last decades. They are indeed involved in many biological processes including translation regulation, pre-mRNA processing, mRNA targeting, telomere maintenance, etc. We have developed chemical tools named TASQ (Template-Assembled Synthetic Quadruplex) to address the following scientific goals: (i) identify unambiguous (i.e., affine and specific) G4- and i-DNA-interacting ligands, (ii) identify proteins interacting with those structures and determine their cellular relevance and (iii) select specific antibodies for G4 and i-DNA. This review reports on our works over the past decade.